Are Guidance and Counseling Teachers Merely Responders? A Conceptual Exploration of Their Role Through Peace Competency - Afanin Halqim; Rahma Hanif (Advances In Education Journal, 2025)
The negative connotation associated with societal perceptions of the guidance and counseling profession sometimes equates it to a problem-solver.  Guidance and counseling educators are essential, beyond conventional academic responsibilities to attend to students' social, emotional, and psychological welfare, while also promoting a pleasant school atmosphere.  This article examines the imperative of peace competency for guidance and counseling educators in the context of inclusive education, and how a peace-oriented approach can transform their function from mere conflict mediators to proactive agents in fostering harmonious, secure, and diversity-respecting educational settings. Utilizing a literary analysis that integrates sources from articles and books released in the last ten years.  The extensive duties of guidance and counseling educators encompass proactive measures to foster a pleasant and inclusive school atmosphere, promote peace education, and prepare students with the competencies required to manage difficult social scenarios and amicably settle problems.  Therefore, support and cooperation from all stakeholders are crucial, including efforts to improve the peace competences of guidance and counseling educators, allowing them to properly execute their roles and responsibilities.